Blood mononuclear cells as speculum of emotional stress analyzed by synchrotron infrared spectroscopy and a nootropic drug - Martinez-Martinez, Alejandro (2018)
Chronic psychological stress is an important public health issue which generates behavioral changes, anxiety, immunosuppression and oxidative damage. Piracetam is a cognitive enhancer, at cellular level it protects from oxidative stress. The aim of this study was to evaluate the effect of psychological stress and of piracetam on circulating mononuclear cells by analyzing the biochemical spectrome using Synchrotron Radiation Fourier Transform Infrared Microspectroscopy (SR-μFTIR). Rats were exposed for five days to a stressor (cat odor) under oral administration of piracetam (600 mg/kg). SR-μFTIR analysis showed a decrease in bands associated to the lipids region (2852 cm−1, 2923 cm−1 and 2962 cm−1) and an increase absorption of the amide I band (1654 cm−1) under stress conditions. The principal component analysis showed increase oxidation of lipids (decrease of 3010 cm−1, 2923 cm−1 and 2852 cm−1 bands) as well as proteins denaturation (increase of 1610 cm−1 and 1690 cm−1 bands) under stress. Piracetam provided protection to polyunsaturated lipids (p ≤ 0.001) and lipids/proteins ratio (p ≤ 0.001). Behaviorally, this drug diminished fear and anxiety in stressed animals by the plus maze test (p ≤ 0.002). However, this drug induced oxidative stress in mononuclear cells from unstressed animals and altered their behavior.